Реклама на нестандартних носіях: класифікаційний аспект - Бойко, Анна С.; Boyko, A. S. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто класифікаційну систему нестандартних рекламоносіїв у контексті сучасного маркетингу. З’ясовано критерії їхнього поділу, загальну характеристику та інші аспекти з урахуванням українських рекламно-інформаційних тенденцій. Проаналізовано можливі варіанти класифікації нетрадиційної реклами. Водночас зроблено спробу, узагальнивши та вдосконаливши уже відому інформацію, представити власну класифікацію нестандартних рекламоносіїв; їхній поділ було здійснено з урахуванням походження рекламоносія, його взаємозв’язку із досягеннями науки та техніки, а також сфери, до якої належить нестандартний рекламний носій. In the article the classification system for custom advertising media. Considered types of ambient advertising division based on criteria such as the type of medium and type of advertising placement. It is noted that any classification can be considered conditional and temporary, since the technology contributes to their marketing material and, accordingly, species growth. In this context also drawn attention to some shortcomings and controversial issues considered separate classifications. An attempt was made correctly interpreting the author's presentation and classification of non-standard media that is complex: on the one hand, it is established (in a slightly modified form) on the basis of existing classifications, but on the other – contains new elements, ie those who were not called or mentioned in passing. Exploration has theoretical and practical importance, since considering and known in modern marketing and information space of non-standard types of advertising, and the most detailed and simplified classification that would be useful to advertisers and those who are interested in effective methods of product promotion.
Advertising on Non-standard Media: Classification Classification Aspect
Keywords: рекламний носій; advertising medium; ambient-медіа; ambient-media; інноваційний маркетинг; innovative marketing; партизанський маркетинг; guerilla marketing; рекламне повідомлення; advertising message